Ecological Distribution of Virulent Multidrug-Resistant Staphylococcus aureus in Livestock, Environment, and Dairy Products - Basma Badawy; Mahmoud Elafify; Alshimaa M. M. Farag; Samar M. Moustafa; Mohamed Z. Sayed-Ahmed; Amira A. Moawad; Abdelazeem M. Algammal; Hazem Ramadan; Mahmoud Eltholth (Antibiotics, 2022)
Staphylococcus aureus is one of the most common causes of mastitis, leading to severe economic losses in the dairy industry. It is also zoonotic, with potential risks to public health. This study aimed to detect the occurrence of S. aureus-resistant strains isolated from cattle, buffalo, their environment, milk and dairy products; and to investigate the extent of animal, ecological, and food contamination by methicillin-resistant (MRSA) or enterotoxigenic S. aureus. Samples (n = 350) were collected from four animal (two cattle and two buffalo) farms, i.e., their environment. Thirty Karish cheese samples were collected from 10 markets in Mansoura, Egypt. S. aureus was detected in 17.9%, 17.6%, and 16.7% of samples collected from cattle, buffalo and Karish cheese, respectively. About 19% of isolated S. aureus strains carried the mecA gene. The distribution of the mecA gene was high in isolates from Karish cheese (60%), followed by samples collected from buffalo (16.2%) and cattle (16%). More than 34% of isolated S. aureus strains were enterotoxigenic, and the presence of enterotoxin genes was higher in isolates from Karish cheese (80%) than those from cattle (48%) and buffalo (18.9%). The most predominant enterotoxin gene among isolated S. aureus strains was the sea gene (26.9%), followed by sec (4.5%) and sed (3%) genes. Isolated strains were resistant to clindamycin (100%), kanamycin (97%), nalidixic acid (86.6%), cefotaxime (73.1%) sulphamethazole—trimethoprim (65.6%). Meanwhile, 95.5%, 94%, 86.6% and 77.7% of S. aureus strains were sensitive to ciprofloxacin, amikacin, imipenem and both cefoxitin and gentamycin, respectively. In conclusion, the presence of enterotoxigenic- and methicillin-resistant S. aureus strains in animals, their environment, and dairy products represents a public health concern, particularly in small-scale dairy farms in Egypt. To reduce the risk of infection of livestock and humans with resistant strains, strict regulations and guidelines for antimicrobial use in such a system are urgently required.